Taxation and mobility in dualistic models – (and) some neglected issues of fiscal federalism - Martins, Ana Paula (2022)
In this paper we present and confront the expected outcome of a raise in earnings taxes on the regional or sectoral allocation of labor force and employment. The basic frameworks are the benchmark dualistic scenarios. A single-input analysis of an homogeneous product economy is provided once extensions were designed to highlight the role of mobility barriers and how they interact with local wage-setting rules to determine regional allocation rather than trade issues or factor substitution. We report the main effects on equilibrium local after-tax wages, supply, employment and aggregate welfare surplus of a unilateral as well as a simultaneous unit tax increase of the (a) basic two-sector model in six different scenarios: free market; partial (one-sector) coverage with perfect intersector mobility; partial (one-sector) coverage with imperfect mobility (Harris-Todaro); multiple (two-sector) coverage with imperfect mobility (Bhagwati-Hamada); partial (one-sector) coverage with affiliation restrictions in the covered sector; partial (one-sector) coverage with limited employment generation ability in the traditional uncovered sector. Needless to say, the results would apply to any other production factor, one or other scenario being more appropriate for inference of the consequences of differential taxation systems.